Interactive effects of users' openness and robot reliability on trust: evidence from psychological intentions, task performance, visual behaviours, and cerebral activations. - Li, Mingming; Guo, Fu; Li, Zhixing; Ma, Haiyang; Duffy, Vincent G. (Ergonomics, 2024)
Although trust plays a vital role in human-robot interaction, there is currently a dearth of literature examining the effect of users' openness personality on trust in actual interaction. This study aims to investigate the interaction effects of users' openness and robot reliability on trust. We designed a voice-based walking task and collected subjective trust ratings, task metrics, eye-tracking data, and fNIRS signals from users with different openness to unravel the psychological intentions, task performance, visual behaviours, and cerebral activations underlying trust. The results showed significant interaction effects. Users with low openness exhibited lower subjective trust, more fixations, and higher activation of rTPJ in the highly reliable condition than those with high openness. The results suggested that users with low openness might be more cautious and suspicious about the highly reliable robot and allocate more visual attention and neural processing to monitor and infer robot status than users with high openness. PRACTITIONER SUMMARY: The study could deepen practitioners' understanding of the effect of openness on trust in robots by examining the psychological intention, task performance, visual behaviours, and physiological activations. Moreover, the interaction effect could provide guidelines for designing robots adaptive to users' personalities, and the multimodal method would be practical for measuring trust in interaction.